Warrior heart, pilgrim soul an immigrant's journey : poems - Smith, Maria Victoria A. Grageda- ([Lexington, Kentucky] Maria Victoria A. Grageda-smith, 2016)
"A collection that chronicles the inherently conflicted yet ultimately rich and textured journey of an immigrant woman compelled to achieve a radical redefinition of individual and national identity against a backdrop of life-changing circumstances and parallel historical developments in the United States and the world"--Back cover.
Keywords: Immigrants -- Poetry; Aliens -- United States -- Poetry; American poetry -- Filipino American authors; Filipino American women -- Poetry